Kommunikationsformen im Zentralkonvent der Templer und Johanniter - Burgtorf, Jochen (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2020)
Forms of Communication in the Central Convent of Templars and Hospitallers The central convent of Templars and Hospitallers was the motherhouse of communities of professed religious. Its forms of communication were based on biblical principles, monastic models, and the specific requirements of their particular charitable, military, and economic pursuits; and they were challenged by the fact that its members hailed from various regions of Latin Christendom and spoke different languages. While the binaries advocated in certain theories of communication (verbal-nonverbal, formal-informal, public-private, etc.) provide useful paradigms, diverse forms of communication in the central convent were interconnected and served to reinforce each other. Covering the twelfth to early fourteenth centuries and based primarily on the Orders’ normative texts, this study focuses on the central convent’s spaces, namely, the church, the refectory, the chapter-hall, the work and leisure areas, and the dormitory, where the close proximity between members necessitated a remarkable array of diverse forms of communication. While it may appear that much of the communication in the central convent was staged, there was need for improvisation; in addition, there were areas in which Templars and Hospitallers differed from each other or in which the sources at least suggest divergent priorities.